Potential Analysis of Snakehead Fish Albumin Extract (Channa striata) as Immunostimulant and Anti-Inflammatory in Indomethacin-Induced Inflammatory Bowel Disease (IBD) Rats - Panjaitan, Tina Fransiskha Carolyn; Fiddaroini, Saidun; Suprayitno, Eddy; Aulanni’am, Aulanni’am; Hardoko, Hardoko (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Inflammatory Bowel Disease (IBD) is a chronic gastrointestinal disorder driven by oxidative stress and immune dysregulation, often exacerbated by prolonged non-steroidal anti-inflammatory drug (NSAID) use. Conventional therapies provide symptomatic relief but are limited by severe adverse effects, necessitating safer alternatives. Channa striata (snakehead fish) is a rich source of albumin, essential amino acids, and bioactive compounds with potential immunomodulatory and anti-inflammatory effects. This study investigates the therapeutic efficacy of purified Channa striata albumin extract in an indomethacin-induced IBD rat model. Albumin was isolated via ammonium sulfate precipitation and characterized by SDS-PAGE, antioxidant activity (DPPH assay), and amino acid profiling. Rats were treated with Channa striata albumin (100-300 mg/kg BW) for 14 days post-indomethacin induction. Compared to controls and diclofenac-treated groups, the extract significantly reduced malondialdehyde (MDA) levels (up to 90.69%), improved jejunal histoarchitecture, and enhanced occludin expression. Immunohistochemistry showed a marked reduction in CD4+T cell infiltration, indicating immunomodulatory activity. These findings establish Channa striata albumin as a potent natural antioxidant and immunomodulator, offering a safer alternative to NSAIDs for IBD management.